Cell-Based Therapies in Acute Kidney Injury (AKI) - Daniel Patschan; Ivo Buschmann; Oliver Ritter; Andreas Kribben (Karger Publishers, 2018)
Acute kidney injury frequently occurs in hospitalized patients all over the world. The prognosis remains poor since specific therapies for promoting kidney regeneration/repair are still missing. In recent years cell-based strategies have improved AKI outcomes under experimental circumstances. Four groups of cells, each of them displaying certain biological and functional characteristics have been evaluated in AKI, induced Pluripotent Stem Cells (iPSCs), Spermatagonial Stem Cells (SSCs), Proangiogenic Cells (PACs) and Endothelial Colony Forming Cells (ECFCs), and Mesenchymal Stem Cells (MSCs). All of these have been documented to stabilize either parameters of kidney excretory dysfunction and/or certain morphological parameters. The mechanisms responsible for AKI protection include direct (cell incorporation) and indirect processes, the latter being mediated by humoral factors and particularly by the production of so-called extracellular vesicles. Cell-derived vesicular organelles have been shown to carry pro-regenerative micro-RNA molecules which stabilize the vascular and tubular function. The first trials in humans have been initiated, the majority of such trials employs MSCs. However, any transfer of cell-based strategies in the clinical practice is potentially associated with significant difficulties. These include cell availability, tolerance and competence. The article intends to summarize essential informations about all of the four populations mentioned above and to discuss implications for the management of human AKI.